Dietary Intakes and Metabolic Disorders - Chiva-Blanch, Gemma; Cofán, Montserrat (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
Metabolic syndrome is defined by a cluster of interrelated cardiovascular risk factors (hyperglycemia, hypertension, dyslipidemia, insulin resistance, and central adiposity), linked to a chronic, systemic, and low-grade inflammation, which severely increases the risk of type II diabetes and cardiovascular disease. A growing body of evidence generated in the last decades has shown that not only the energy balance but also the macro-, micro-, and non-nutrient composition of the diet may influence the onset and progression of metabolic syndrome. However, further research is required to increase our understanding about the contribution of diet to metabolic syndrome prevention.